(untitled) (Jurnal Bahasa, 2014)
Language plays an important role in describing personality and identity of a community, while the Malays are the native speakers of Malay Language. Therefore, the objectives of this study are to examine the Malay language used in social networking such as Facebook and to explore the impact of English on the identity of Malays. A total of 70 Malay respondents were selected, and data was collected through an online questionnaire. Then, the responses to the questionnaire were analyzed quantitatively and qualitatively. The results show that English is a an increasingly strong influence on the Malay language. This is due to confusion in the self-identity of the speakers. Finally, this study is important to give the real picture of the state of the Malay language among Malays in Malaysia. Keywords: code-mixing, code-switching, identity, ethnic Malays, Facebook